The 6 most important decisions you$1 (Bll ever make : s a guide for teens - Covey, Sean. (New York : Fireside, 2006)
The challenges teens face today are tougher than at any time in history: academic stress, parent communication, media bombardment, dating drama, abuse, bullying, addictions, depression, and peer pressure, just to name a few. And, like it or not, the choices teens make while navigating these challenges can make or break their futures. In The 6 Most Important Decisions You'll Ever Make, Sean Covey, author of the international bestseller The 7 Habits of Highly Effective Teens, gives teens the strong advice they need to make informed and wise decisions.Using real stories from teens around the world, Sean shows teens how to succeed in school, make good friends, get along with parents, wisely handle dating and sex issues, avoid or overcome addictions, build self-esteem, and much more. Jam-packed with original cartoons, inspiring quotes, and fun quizzes, this innovative book will help teens not only survive but thrive during their teen years and beyond.
School -- I'm Totally Stressed Out! -- Surviving and Thriving -- Off to College -- Finding Your Voice -- Friends -- So Fun . . . So Fickle -- Surviving the Everyday Ups and Downs of Friendships -- Making and Being a Friend -- Peer Pressure -- Parents -- How Embarrassing -- The Relationship Bank Account -- You're So Annoying -- Closing the Gap -- When You Have to Raise Your Parents -- Dating & Sex -- Do We Have to Talk About This? -- The Four Great Sex Myths -- Intelligent Dating -- Love Waits -- Addictions -- It's Not Hard to Quit . . . I've Done It a Dozen Times -- Three Brutal Realities -- The Truth, the Whole Truth, and Nothing but Striking at the Root -- Self-Worth If Only I Were Better Looking -- The Social Mirror and the True Mirror-- Character and Competence -- Conquering Your El Guapo! -- Stick to the Code -- It's Worth Fighting For!.
"A Fireside Book."
Includes bibliographical references (p. 310-311) and index.
1
Keywords: Teenagers -- Conduct of life; Teenagers -- Life skills guides; Decision making in adolescence